Is the Master Civil Liable Based on Sea Freight Arrangements in Indonesia? - Ratnawati, Elfrida; Wijaya, Vience Ratna Multi; Budhianti, Meta Indah; Sobirov, Bobur Baxtishodovich (Lembaga Contrarius Indonesia, 2024)
This research aims to analyze the regulations regarding the civil liability of the master based on the Maritime Transport Regulations in Indonesia. This research is normative legal research using secondary data and a statutory regulatory approach. The research results show that, first, if the captain, in carrying out his duties and authority, causes losses to shippers or passengers, including other material losses, due to his negligence, mistake, or error, then the master is not civilly responsible; however, if the master is due to negligence, mistake, or mistake, causing damage or destruction to the goods being transported or passengers suffering minor injuries, serious injuries, permanent disability, or death. Second, the weaknesses in the current regulation of ship worker responsibilities consist of legal weaknesses in terms of legal substance, where the responsibilities of ship workers have not been regulated strictly in the shipping law, and weaknesses in terms of legal structure, namely the legal understanding of law enforcement officials, which is still lacking in action. Shipping Crimes: There is no Special Court for Shipping Crimes, and Human Resources for Law Enforcement Officers for Shipping Crimes still needs to be improved.